Telling tomorrows: Science fiction as an energy futures research tool. (September 2017) - Raven, Paul Graham
Abstract: Any sociological discussion of energy consumption must necessarily deal with not only the social practices underpinning that consumption, but also the complex sociotechnical assemblages through which such consumption is enabled. Likewise any sociological discussion of climate change must necessarily deal with not only radically different contexts, but also the inherent uncertainty that accompanies any exploration of times yet to come. There are many ways in which one might narrate and/or critique such futures, but few which can handle all of the challenges mentioned above. Such work requires a medium and methodology which can: represent the social alongside the technological; move fluidly between micro, meso and macro scales; reconcile historical trajectories with extrapolated trends and speculative leaps; and – perhaps most importantly—speak across (and beyond) the disciplinary and administrative silos of both the state and the academy. This paper makes a case for the utility of prose science fiction both as a methodological tool of representation and portrayal for energy futures research which meets these criteria, and as a storehouse of tools and strategies for the critique of energy futures.